2019
DOI: 10.1038/s41598-019-47343-w
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatic analysis identifies circadian expression of splicing factors and time-dependent alternative splicing events in the HD-MY-Z cell line

Abstract: The circadian clock regulates key cellular processes and its dysregulation is associated to several pathologies including cancer. Although the transcriptional regulation of gene expression by the clock machinery is well described, the role of the clock in the regulation of post-transcriptional processes, including splicing, remains poorly understood. In the present work, we investigated the putative interplay between the circadian clock and splicing in a cancer context. For this, we applied a computational pip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 90 publications
2
10
0
Order By: Relevance
“…While the 8-h gene set showed an enrichment of terms related to metabolism, the 12-h set showed an enrichment of terms related to endoplasmic reticulum (ER)-related processes, splicing, translation and gene expression regulation. The 24-h rhythmically expressed genes showed an enrichment of terms related to meiosis, and splicing (Figure S3), which is in line with our previous findings [25,26,27,28].…”
Section: Resultssupporting
confidence: 91%
“…While the 8-h gene set showed an enrichment of terms related to metabolism, the 12-h set showed an enrichment of terms related to endoplasmic reticulum (ER)-related processes, splicing, translation and gene expression regulation. The 24-h rhythmically expressed genes showed an enrichment of terms related to meiosis, and splicing (Figure S3), which is in line with our previous findings [25,26,27,28].…”
Section: Resultssupporting
confidence: 91%
“…For some time now, evidence has been accumulating pointing to the fact that AS can affect clock components and, that mutations affecting spliceosome related components can alter the circadian period (12,13,16,17,44). Furthermore, studies performed in fruit flies, mice and human cell lines have identified a role for the circadian clock in the control of the splicing process (45-47). Yet there have been no global transcriptomic studies that allowed for understanding the extent of clock control on AS on any plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also found that splicing-related genes have temporal expression patterns that oscillate every 24 h [90][91][92]. Alternative splicing of U2-auxiliary-factor 26 has been shown to destabilize PER1 in mice [90].…”
Section: Mutations Epigenetic Changes and Deregulated Expression Of mentioning
confidence: 99%